1999
DOI: 10.1557/jmr.1999.0413
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical anisotropy behavior in Pb0.88Eu0.08Ti1−yMnyO3 system: Role of 90° domain reversal

Abstract: An indirect observation of 90°domain reversal under the influence of a poling field process was undertaken by an x-ray diffraction study in the Pb 0.88 Eu 0.08 Ti 1−y Mn y O 3 (y ‫ס‬ 0, 0.01, 0.02, and 0.03) piezoelectric anisotropic system. The optimum condition k p → 0 was achieved for y ‫ס‬ 0.02 composition. A large percentage of 90°domain rotation was necessary, but not a sufficient condition for the ultrahigh electromechanical anisotropy manifestation. A large microstrain originated by structural defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The ionic radius of the Mn 2+ ion is similar to that of the Ti 4+ ion (0.81 and 0.74 Å, respectively, considering the corresponding coordination number for the B site of the perovskite structure) [20] and thereby upon manganese substitution an important effect on the structural parameters is not expected. Note that we have considered Mn 2+ because previous studies have shown that a Mn 4+ /Mn 2+ reduction takes place during the sintering process for this type of materials [10,18,19].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ionic radius of the Mn 2+ ion is similar to that of the Ti 4+ ion (0.81 and 0.74 Å, respectively, considering the corresponding coordination number for the B site of the perovskite structure) [20] and thereby upon manganese substitution an important effect on the structural parameters is not expected. Note that we have considered Mn 2+ because previous studies have shown that a Mn 4+ /Mn 2+ reduction takes place during the sintering process for this type of materials [10,18,19].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that PbTiO 3 (PT) undergoes a single ferroelectric transition from cubic to tetragonal [1] at around 490 • C, whereby the polar tetragonal state is stabilized by the large tetragonal strain in the c axis brought about by Pb-O hybridization. Systematic studies of the crystal structures, microstructures and electrical properties on modified PT have been developed in the last decades [1][2][3][4][5][6][7][8][9][10][11][12]. The sintering of pure PT ceramics is very difficult because of the large tetragonality, which it has been shown can be reduced greatly by the partial substitution of the Pb 2+ or Ti 4+ ions [1][2][3][4][5][6][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations